FORMATION OF LEXICAL SKILLS IN THE PROCESS OF TEACHING ENGLISH LANGUAGE - Abdikalyk, A.N.; Kudritskaya, M.I (PUBLISHINGS of Kostanay State Pedagogical Institute, 2017)
This article deals with the notion of lexical skills, structure, qualities, stable conditions for the formation of lexical skills, as well as steps that passes every new lexical unit. All this must be taken into account in the process of learning a foreign language vocabulary. There are effective types of exercises that form and develop students’ lexical skills in the English language. The classification of lexical exercises according to different principles is given
Keywords: lexical exercise; teaching materials; foreign language teaching; methodical classification